Copper sulfide-platinum net-shaped ultrathin nanosheet and preparation method and application thereof

通过置换反应制备硫化铜-铂超薄纳米片,调控其网状结构,解决了硫化铜-铂纳米材料催化光降解性能不足的问题,实现了高效的光降解效果。

CN119633852AActive Publication Date: 2025-03-18JINING UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411813549.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

How to effectively regulate the microstructure of copper sulfide-platinum nanomaterials to improve its catalytic photodegradation performance.

Method used

Copper sulfide-platinum sulfide ultrathin nanosheets were prepared by replacement reactions, and their mesh structure was regulated to form nanosheets with porous and ultrathin structures.

Benefits of technology

The two-dimensional network structure regulation of copper sulfide-platinum nanosheets was achieved, which improved its performance in photocatalytic degradation, especially in degrading methylene blue dyes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633852A_ABST
    Figure CN119633852A_ABST
Patent Text Reader

Abstract

The invention relates to a copper sulfide-platinum reticular ultrathin nanosheet as well as a preparation method and application thereof. The microstructure of the nanosheet is a two-dimensional reticular structure consisting of copper sulfide and platinum. The copper sulphide-platinum ultrathin nanosheet is prepared through a replacement reaction means, and the net structure of the copper sulphide-platinum nanosheet is effectively regulated and controlled, so that the catalytic photodegradation performance of the copper sulphide-platinum ultrathin nanosheet is improved. The porous structure and the ultrathin structure of the copper sulfide-platinum netted ultrathin nanosheet are beneficial to providing abundant active sites, high specific surface area, efficient charge transfer and the like, and can provide better photodegradation efficiency. The preparation steps are simple, reactants are low in toxicity, hazardous chemicals are not contained, and the process is green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of two-dimensional multi-metal mixed nanomaterials, and specifically relates to a mesh copper sulfide-platinum hollow ultra-thin nanosheet, a preparation method thereof, and a catalytic degradation application thereof. Background Art

[0002] Metal hybrid nanomaterials have important applications in the fields of catalysis, environmental science, biomedicine, energy, information technology, military equipment, aerospace, etc. For example: CN110918017A discloses a method for preparing a precious metal / copper sulfide core-shell structure nanocrystal, and the prepared precious metal / copper sulfide core-shell structure nanocrystal has a significantly improved efficiency in degrading toxic gases such as formaldehyde compared to single-structure copper sulfide nanocrystal. CN110794017A discloses a method for preparing an electrochemical immunosensor for detecting procalcitonin by platinum nanoparticle functionalized flower-shaped copper oxysulfide, using platinum nanoparticle functionalized flower-shaped copper oxysulfide as a base material, using a phosphate buffer solution containing hydrogen peroxide as a base liquid, and using a layer-by-layer modification method of an electrochemical sensor to construct a signal-attenuated electrochemical immunosensor, improve the sensor sensitivity and detection limit, and achieve rapid and efficient detection of procalcitonin. CN116019923A discloses a preparation method and application of a copper sulfide nano drug encapsulating a tetravalent platinum prodrug. The prepared copper sulfide nano drug carrier has good hydrophilicity, is conducive to circulation and distribution in the body, and has good photothermal effect in the body.

[0003] The microstructure of nanomaterials has an important influence on their performance. Two-dimensional metal hybrid nanomaterials have attracted extensive attention due to their unique characteristics such as large surface area, spatial confinement effect and tunable electronic properties. Nanomaterials composed of copper sulfide (CuS) and platinum (Pt) combine the semiconductor properties of CuS with the catalytic efficiency and metal stability of Pt, showing unique synergistic properties, which is of great significance for enhancing catalytic activity and photoelectric performance as well as multifunctionality for environmental degradation, energy and biomedical applications. How to effectively regulate the microstructure of copper sulfide-platinum nanomaterials to improve their catalytic photodegradation performance is a technical problem that needs to be solved urgently. To this end, the present invention is proposed. Summary of the invention

[0004] In view of the above technical status, the present invention prepares copper sulfide-platinum ultrathin nanosheets by means of replacement reaction, effectively regulates the network structure of copper sulfide-platinum nanosheets, thereby improving its catalytic photodegradation performance.

[0005] Therefore, the first object of the present invention is to provide a copper sulfide-platinum network ultra-thin nanosheet, which is a nanosheet with different pore structures.

[0006] The second object of the present invention is to provide a method for preparing copper sulfide-platinum network ultra-thin nanosheets.

[0007] The third object of the present invention is to provide application of copper sulfide-platinum mesh ultra-thin nanosheets in catalytic photodegradation.

[0008] The technical solution for achieving the above-mentioned invention object can be summarized as follows:

[0009] Copper sulfide-platinum mesh ultra-thin nanosheets, the microstructure of which is a two-dimensional mesh structure composed of copper sulfide and platinum.

[0010] According to the present invention, preferably, the copper sulfide-platinum mesh ultra-thin nanosheet has a thickness of 0.5-20 nm.

[0011] According to the present invention, preferably, in the copper sulfide-platinum mesh ultra-thin nanosheets, the molar ratio of copper sulfide to platinum is (5-150):1.

[0012] According to the present invention, the method for preparing the above copper sulfide-platinum mesh ultra-thin nanosheets comprises the following steps:

[0013] (1) adding a sulfur source and a copper salt to an organic solvent A and mixing them evenly, reacting them at a certain temperature for a period of time, washing them with an organic solvent B, separating and purifying them, and then dispersing them into the organic solvent A;

[0014] (2) Adding platinum salt to step (1), reacting at a certain temperature for a period of time, washing with an organic solvent B, separating and purifying, and obtaining the final product, copper sulfide-platinum mesh ultrathin nanosheets.

[0015] According to the present invention, preferably, in step (1), the sulfur source is one of sulfur powder, glutathione, sodium thiosulfate, L-cysteine, and L-cystine, and more preferably sulfur powder;

[0016] Preferably, the copper salt is one of copper chloride, copper bromide, copper sulfate, copper nitrate, copper acetate, and copper acetylacetonate, and more preferably copper acetylacetonate;

[0017] Preferably, the organic solvent A is one of benzyl alcohol, oleylamine, bis(2-hydroxyethyl)oleylamine, oleylpropylenediamine and oleic acid, and more preferably oleylpropylenediamine.

[0018] According to the present invention, preferably, in step (1), the molar ratio of the sulfur source to the copper salt is (0.5-20):1.

[0019] According to the present invention, preferably, in step (1), the certain temperature is in the range of 50-250°C, more preferably 100-200°C, and most preferably 150°C;

[0020] Preferably, the period of time ranges from 0.5 to 10 hours, more preferably from 1 to 2 hours, and most preferably from 1 hour.

[0021] According to the present invention, preferably, in step (2), the platinum salt is one of platinous chloride, platinum acetylacetonate, platinum chloride, and chloroplatinic acid, and more preferably chloroplatinic acid;

[0022] Preferably, the organic solution B is one of cyclohexane, toluene, ethyl acetate, dichloromethane and tetrahydrofuran, and more preferably cyclohexane.

[0023] According to the present invention, preferably, in step (2), the certain temperature is in the range of 50-300°C, more preferably 100-250°C, and most preferably 220°C;

[0024] Preferably, the period of time ranges from 0.5 to 10 hours, more preferably from 1 to 2 hours, and most preferably from 1 hour.

[0025] According to the present invention, preferably, the molar ratio of the copper salt in step (1) to the platinum salt in step (2) is (0.5-150):1.

[0026] According to the present invention, preferably, in steps (1) and (2), the separation and purification method is at least one of centrifugation, filtration and decantation, and centrifugation is more preferably used.

[0027] According to the present invention, the copper sulfide-platinum mesh ultra-thin nanosheets are used for photocatalytic degradation; preferably for photocatalytic degradation of methylene blue dye.

[0028] Beneficial effects of the present invention:

[0029] 1. The present invention realizes the effective regulation of the two-dimensional network structure of copper sulfide-platinum nanosheets for the first time, obtains nanosheets with different pore structures, and expands the limitations of the morphological structure of the material.

[0030] 2. The copper sulfide-platinum mesh ultrathin nanosheets prepared by the present invention can be used as a catalyst for photocatalytic degradation. Its porous structure and ultrathin structure are conducive to providing abundant active sites, high specific surface area, efficient charge transfer, etc., and can provide better photodegradation efficiency.

[0031] 3. The preparation steps of the copper sulfide-platinum mesh ultra-thin nanosheets of the present invention are simple, the reactants are low-toxic, no hazardous chemicals are contained, and the process is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 .This is a transmission electron microscope photograph of the product prepared in Example 1 of the present invention.

[0033] Figure 2. X-ray diffraction pattern of the product prepared in Example 1 of the present invention, and comparison with standard PDF cards of CuS and Pt.

[0034] Figure 3 . This is the UV-visible absorption spectrum of the product prepared in Example 1 of the present invention, and the comparison with copper sulfide nanosheets.

[0035] Figure 4 . This is the UV-visible light absorption spectrum of the solution of the product prepared in Example 1 of the present invention, which changes with time during the process of catalyzing the photodegradation of methylene blue dye.

[0036] Figure 5 The product prepared in Example 1 of the present invention is catalyzed by the photodegradation of methylene blue dye. The concentration of methylene blue at different reaction times (C t ) to the initial concentration (C0) over time.

[0037] Figure 6 . The product prepared in Example 1 of the present invention is catalyzed in the photodegradation process of methylene blue dye, ln (C t / C0) values ​​and fitting straight lines at different irradiation times, the apparent reaction constant is 0.311min -1 .

[0038] Figure 7 . is the conversion rate of five cycles of photodegradation of methylene blue dye catalyzed by the product prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The present invention prepares copper sulfide-platinum ultrathin nanosheets by means of a replacement reaction, and effectively regulates the network structure of the copper sulfide-platinum nanosheets, thereby improving the catalytic photodegradation performance thereof.

[0040] The copper sulfide-platinum mesh ultra-thin nanosheet of the present invention has a microstructure of a mesh two-dimensional ultra-thin sheet formed by a copper sulfide-platinum composite. The porous structure and ultra-thin structure thereof are conducive to providing abundant active sites, high specific surface area, efficient charge transfer, etc., and can provide better photodegradation efficiency.

[0041] In one or more preferred embodiments, the copper sulfide-platinum network ultra-thin nanosheet has a thickness of 0.5-20 nm.

[0042] In one or more preferred embodiments, in the copper sulfide-platinum mesh ultra-thin nanosheets, the molar ratio of copper sulfide to platinum is (5-150):1, for example: 20:1, 30:1, 50:1, 80:1, 100:1, 120:1.

[0043] According to the present invention, a method for preparing a copper sulfide-platinum mesh ultra-thin nanosheet comprises the following steps:

[0044] (1) adding a sulfur source and a copper salt to an organic solvent A and mixing them evenly, reacting them at a certain temperature for a period of time, washing them with an organic solvent B, separating and purifying them, and then dispersing them into the organic solvent A;

[0045] (2) Adding platinum salt to step (1), reacting at a certain temperature for a period of time, washing with an organic solvent B, separating and purifying, and obtaining the final product, copper sulfide-platinum mesh ultrathin nanosheets.

[0046] According to the present invention, step (1) is a process for preparing copper sulfide nanosheets, and the thickness of the nanosheets can be regulated by adjusting the ratio of the sulfur source and the copper salt and adjusting the type of the copper salt.

[0047] In one or more preferred embodiments, the sulfur source is one of sulfur powder, glutathione, sodium thiosulfate, L-cysteine, and L-cystine, and more preferably sulfur powder.

[0048] In one or more preferred embodiments, the copper salt is one of copper chloride, copper bromide, copper sulfate, copper nitrate, copper acetate, and copper acetylacetonate, and more preferably copper acetylacetonate.

[0049] In one or more preferred embodiments, the organic solvent A is one of benzyl alcohol, oleylamine, bis(2-hydroxyethyl)oleylamine, oleylpropylenediamine, and oleic acid, and more preferably oleylpropylenediamine.

[0050] In one or more preferred embodiments, the molar ratio of the sulfur source to the copper salt in step (1) is (0.5-20):1.

[0051] In one or more preferred embodiments, the certain temperature in step (1) is in the range of 50-250°C, more preferably 100-200°C, and most preferably 150°C;

[0052] Preferably, the period of time ranges from 0.5 to 10 hours, more preferably from 1 to 2 hours, and most preferably from 1 hour.

[0053] According to the present invention, step (2) is a process for preparing copper sulfide-platinum mesh nanosheets. The thickness of the thin layer can be adjusted by controlling the temperature, and the pore structure can be adjusted by changing the amount of platinum salt added.

[0054] In one or more preferred embodiments, the platinum salt is one of platinous chloride, platinum acetylacetonate, platinum chloride, and chloroplatinic acid, and is further preferably chloroplatinic acid;

[0055] Preferably, the organic solution B is one of cyclohexane, toluene, ethyl acetate, dichloromethane and tetrahydrofuran, and more preferably cyclohexane.

[0056] In one or more preferred embodiments, in step (2), the certain temperature is in the range of 50-300°C, more preferably 100-250°C, and most preferably 220°C;

[0057] Preferably, the period of time ranges from 0.5 to 10 hours, more preferably from 1 to 2 hours, and most preferably from 1 hour.

[0058] In one or more preferred embodiments, the molar ratio of the copper salt in step (1) to the platinum salt in step (2) is (0.5-150):1.

[0059] In one or more preferred embodiments, in steps (1) and (2), the separation and purification method is at least one of centrifugation, filtration, and decantation, and centrifugation is more preferred.

[0060] According to the present invention, the copper sulfide-platinum mesh ultra-thin nanosheets are used for photocatalytic degradation; preferably for photocatalytic degradation of methylene blue dye.

[0061] Example 1

[0062] 10 mg of copper acetylacetonate and 10 mg of sulfur powder were added to 10 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. Washed with 10 mL of cyclohexane, purified by centrifugation, and redispersed in 10 mL of oleyl propylene diamine. 50 μL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. Washed with 10 mL of cyclohexane, purified by centrifugation, and obtained the final product.

[0063] Example 2

[0064] 15 mg of copper nitrate and 20 mg of sulfur powder were added to 20 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 15 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 20 mL of oleyl propylene diamine. 200 μL of 50 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 10 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0065] Example 3

[0066] 50 mg of copper chloride and 120 mg of sulfur powder were added to 100 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 50 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 100 mL of oleyl propylene diamine. 0.5 mL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 50 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0067] Example 4

[0068] 0.5 g of copper acetylacetonate and 0.8 g of sulfur powder were added to 500 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 150 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 300 mL of oleyl propylene diamine. 1 mL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 100 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0069] Example 5

[0070] 80 mg of copper acetylacetonate and 100 mg of sulfur powder were added to 100 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 50 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 80 mL of oleyl propylene diamine. 0.3 mL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 60 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0071] Example 6

[0072] 100 mg of copper acetylacetonate and 50 mg of glutathione were added to 100 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 80 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 100 mL of oleyl propylene diamine. 50 μL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 50 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0073] Example 7

[0074] 200 mg of copper acetylacetonate and 150 mg of sodium thiosulfate were added to 200 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 100 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 200 mL of oleyl propylene diamine. 1 mL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 80 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0075] Example 8

[0076] 1g of copper acetylacetonate and 1g of sulfur powder were added to 500mL of oleylamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 500mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 300mL of oleyl propylene diamine. 6mL of 100mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 300mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0077] Example 9

[0078] 0.5g of copper acetylacetonate and 0.5g of sulfur powder were added to 300mL of benzyl alcohol and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 250mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 250mL of oleyl propylene diamine. 2mL of 100mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 200mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0079] Example 10

[0080] 0.6g of copper acetylacetonate and 0.4g of sulfur powder were added to 500mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 300mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 500mL of oleyl propylene diamine. 1mL of 100mM chloroplatinic acid solution was further added, and reacted at 220 degrees Celsius for 1 hour. 300mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0081] Embodiment 11

[0082] 50 mg of copper acetylacetonate and 50 mg of sulfur powder were added to 50 mL of oleyl propylene diamine and mixed evenly, and reacted at 50 degrees Celsius for 1 hour. 30 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 60 mL of oleyl propylene diamine. 45 μL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 80 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0083] Example 12

[0084] 30 mg of copper acetylacetonate and 40 mg of sulfur powder were added to 30 mL of oleyl propylene diamine and mixed evenly, and reacted at 250 degrees Celsius for 1 hour. 30 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 30 mL of oleyl propylene diamine. 100 μL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 30 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0085] Embodiment 13

[0086] 10 mg of copper acetylacetonate and 8 mg of sulfur powder were added to 10 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 0.5 hours. Washed with 10 mL of cyclohexane, purified by centrifugation, and redispersed in 10 mL of oleyl propylene diamine. 45 μL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. Washed with 10 mL of cyclohexane, purified by centrifugation, and obtained the final product.

[0087] Embodiment 14

[0088] 150 mg of copper acetylacetonate and 150 mg of sulfur powder were added to 200 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 10 hours. 80 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 150 mL of oleyl propylene diamine. 600 μL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 100 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0089] Embodiment 15

[0090] 250 mg of copper acetylacetonate and 400 mg of sulfur powder were added to 300 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 150 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 200 mL of oleyl propylene diamine. 50 mg of platinum acetylacetonate was added, and reacted at 220 degrees Celsius for 1 hour. 100 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0091] Example 16

[0092] 30 mg of copper acetylacetonate and 30 mg of sulfur powder were added to 30 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. Washed with 20 mL of cyclohexane, purified by centrifugation, and redispersed in 30 mL of oleyl propylene diamine. 0.15 mL of 100 mM platinum chloride was added, and reacted at 220 degrees Celsius for 1 hour. Washed with 20 mL of cyclohexane, purified by centrifugation, and obtained the final product.

[0093] Embodiment 17

[0094] 800 mg of copper acetylacetonate and 500 mg of sulfur powder were added to 800 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 300 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 500 mL of oleylamine. 5 mL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 400 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0095] Embodiment 18

[0096] 300 mg of copper acetylacetonate and 300 mg of sulfur powder were added to 400 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 300 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 300 mL of bis(2-hydroxyethyl)oleyl amine. 200 μL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 200 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0097] Embodiment 19

[0098] 40 mg of copper acetylacetonate and 80 mg of sulfur powder were added to 80 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. Washed with 50 mL of toluene, purified by centrifugation, and redispersed in 40 mL of oleyl propylene diamine. 100 μL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. Washed with 30 mL of toluene, purified by centrifugation, and obtained the final product.

[0099] Embodiment 20

[0100] 60 mg of copper acetylacetonate and 50 mg of sulfur powder were added to 50 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. Washed with 50 mL of dichloromethane, purified by centrifugation, and redispersed in 50 mL of oleyl propylene diamine. 600 μL of 50 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. Washed with 50 mL of dichloromethane, purified by centrifugation, and the final product was obtained.

[0101] Embodiment 21

[0102] 25 mg of copper acetylacetonate and 25 mg of sulfur powder were added to 25 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. Washed with 20 mL of cyclohexane, purified by centrifugation, and redispersed in 25 mL of oleyl propylene diamine. 100 μL of 100 mM chloroplatinic acid solution was added, and reacted at 50 degrees Celsius for 1 hour. Washed with 20 mL of cyclohexane, purified by centrifugation, and obtained the final product.

[0103] Embodiment 22

[0104] 1.2 g of copper acetylacetonate and 1.2 g of sulfur powder were added to 1 L of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 800 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 800 mL of oleyl propylene diamine. 60 mL of 100 mM chloroplatinic acid solution was added, and reacted at 300 degrees Celsius for 1 hour. 800 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0105] Embodiment 23

[0106] 100 mg of copper acetylacetonate and 100 mg of sulfur powder were added to 100 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 150 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 100 mL of oleyl propylene diamine. 0.5 mL of 100 mM chloroplatinic acid solution was added, and the mixture was reacted at 220 degrees Celsius for 0.5 hour. 100 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0107] Embodiment 24

[0108] 50 mg of copper acetylacetonate and 40 mg of sulfur powder were added to 40 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 30 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 40 mL of oleyl propylene diamine. 250 μL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 10 hours. 40 mL of cyclohexane was used for washing, purified by centrifugation, and the final product was obtained.

[0109] Embodiment 25

[0110] 300 mg of copper acetylacetonate and 300 mg of sulfur powder were added to 500 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 300 mL of cyclohexane was used for washing, separated and purified by decantation, and redispersed in 250 mL of oleyl propylene diamine. 1 mL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 200 mL of cyclohexane was used for washing, and the mixture was purified by centrifugation to obtain the final product.

[0111] Embodiment 26

[0112] 2g of copper acetylacetonate and 2g of sulfur powder were added to 2L of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 1.5L of cyclohexane was used for washing, separated and purified by filtration, and redispersed in 1L of oleyl propylene diamine. 10mL of 100mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 1L of cyclohexane was used for washing, and the mixture was purified by centrifugation to obtain the final product.

[0113] Embodiment 27

[0114] 800 mg of copper acetylacetonate and 800 mg of sulfur powder were added to 800 mL of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 1 hour. 500 mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 600 mL of oleyl propylene diamine. 5 mL of 100 mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 1 L of cyclohexane was used for washing, separated and purified by decantation, and the final product was obtained.

[0115] Embodiment 28

[0116] 1g of copper acetylacetonate and 1g of sulfur powder were added to 1L of oleyl propylene diamine and mixed evenly, and reacted at 150 degrees Celsius for 10 hours. 800mL of cyclohexane was used for washing, purified by centrifugation, and redispersed in 1L of oleyl propylene diamine. 5mL of 100mM chloroplatinic acid solution was added, and reacted at 220 degrees Celsius for 1 hour. 1L of cyclohexane was used for washing, and the mixture was separated and purified by filtration to obtain the final product.

[0117] Test Example 1

[0118] Test Example: Transmission electron microscope photo of the final product prepared, such as Figure 1 As shown. Figure 1 It can be seen that the copper sulfide-platinum mesh ultra-thin nanosheets present a mesh structure.

[0119] Test Example 2

[0120] Test Example: The X-ray diffraction spectrum of the final product, copper sulfide-platinum mesh ultra-thin nanosheets, is as follows: Figure 2 As shown. Figure 2 It can be seen that by comparing with the standard PDF cards of platinum and copper sulfide, the main component of the ultra-thin nanosheet crystals is copper sulfide structure, and the diffraction peak signal of metal Pt is weak due to its low content.

[0121] Test Example 3

[0122] Test Example: The UV-visible absorption spectra of the final product copper sulfide-platinum mesh ultrathin nanosheets and the solid copper sulfide nanosheets of the comparative sample are as follows: Figure 3 As shown. Figure 3 It can be seen that the copper sulfide-platinum mesh ultrathin nanosheet cyclohexane suspension has strong absorption in the visible light region.

[0123] Test Example 4

[0124] Test Example: Testing the application performance of the final product, copper sulfide-platinum mesh ultrathin nanosheets, in photocatalytic degradation of methylene blue dye, such as Figure 4 , as shown in Figures 5, 6, and 7.

[0125] In the methylene blue photodegradation process, three solutions were first prepared: copper sulfide-platinum nanosheet solution (1 mg mL -1 ), methylene blue solution (50 mg·L -1 ) and H2O2 solution (concentration of 3.32×10 -2 mol·L -1 ). These solutions were mixed at a molar ratio of 1:1:40 to obtain 20 mL of an aqueous solution.

[0126] A 300W xenon lamp was used to irradiate the mixed solution of copper sulfide-platinum mesh ultrathin nanosheets, methylene blue and hydrogen peroxide, and the reaction was stirred at 6°C. Figure 4 It can be seen that as the irradiation time of the light source increases, the absorbance of the solution gradually decreases. Figure 5 It can be seen that the ratio of the concentration of methylene blue at different reaction times to the initial concentration decreases as the reaction time increases. Figure 6It can be seen that the apparent reaction constant of methylene blue degradation under the catalysis of copper sulfide-platinum mesh ultrathin nanosheets is 0.311min -1 .Depend on Figure 7 It can be seen that after five cycles of use of copper sulfide-platinum mesh ultrathin nanosheets to catalyze the photodegradation of methylene blue dye, the conversion rate did not decrease compared with the initial reaction.

Claims

1. Copper sulfide-platinum mesh ultra-thin nanosheets, characterized in that: The microstructure of the nanosheet is a two-dimensional network structure composed of copper sulfide and platinum.

2. The copper sulfide-platinum mesh ultra-thin nanosheet according to claim 1, characterized in that: The copper sulfide-platinum mesh ultra-thin nanosheet has a thickness of 0.5-20 nm.

3. The copper sulfide-platinum mesh ultra-thin nanosheet according to claim 1, characterized in that: In the copper sulfide-platinum mesh ultra-thin nanosheet, the molar ratio of copper sulfide to platinum is (5-150):

1.

4. The method for preparing the copper sulfide-platinum mesh ultra-thin nanosheet according to any one of claims 1 to 3, comprising the following steps: (1) adding a sulfur source and a copper salt to an organic solvent A and mixing them evenly, reacting them at a certain temperature for a period of time, washing them with an organic solvent B, separating and purifying them, and then dispersing them into the organic solvent A; (2) Adding platinum salt to step (1), reacting at a certain temperature for a period of time, washing with an organic solvent B, separating and purifying, and obtaining the final product, copper sulfide-platinum mesh ultrathin nanosheets.

5. The method for preparing the copper sulfide-platinum mesh ultra-thin nanosheet according to claim 4, characterized in that: In step (1), the sulfur source is one of sulfur powder, glutathione, sodium thiosulfate, L-cysteine, and L-cystine; Preferably, the copper salt is one of copper chloride, copper bromide, copper sulfate, copper nitrate, copper acetate, and copper acetylacetonate; Preferably, the organic solvent A is one of benzyl alcohol, oleylamine, bis(2-hydroxyethyl)oleylamine, oleylpropylenediamine and oleic acid.

6. The method for preparing the copper sulfide-platinum mesh ultra-thin nanosheet according to claim 4, characterized in that: In step (1), the molar ratio of the sulfur source to the copper salt is (0.5-20):

1.

7. The method for preparing the copper sulfide-platinum network ultra-thin nanosheet according to claim 4, characterized in that: In step (1), the certain temperature ranges from 50 to 250° C.; Preferably, the period of time ranges from 0.5 to 10 hours.

8. The method for preparing the copper sulfide-platinum network ultra-thin nanosheet according to claim 4, characterized in that: In step (2), the platinum salt is one of platinous chloride, platinum acetylacetonate, platinum chloride, and chloroplatinic acid; Preferably, the organic solution B is one of cyclohexane, toluene, ethyl acetate, dichloromethane and tetrahydrofuran.

9. The method for preparing the copper sulfide-platinum network ultra-thin nanosheet according to claim 4, characterized in that: In step (2), the certain temperature ranges from 50 to 300° C.; Preferably, the period of time ranges from 0.5 to 10 hours; Preferably, the molar ratio of the copper salt in step (1) to the platinum salt in step (2) is (0.5-150):

1.

10. Use of the copper sulfide-platinum mesh ultrathin nanosheets according to any one of claims 1 to 4 for photocatalytic degradation; preferably for photocatalytic degradation of methylene blue dye.

Citation Information

Patent Citations

  • Preparation method of electrochemical immunosensor for detecting procalcitonin by platinum nanoparticle-functionalized flower-like copper oxysulfide

    CN110794017A

  • Preparation method of precious metal / copper sulfide core-shell structure nanocrystalline

    CN110918017A

  • Preparation method and application of copper sulfide nano-drug entrapped with tetravalent platinum prodrug

    CN116019923A

  • Three-dimensional material based on copper sulfide lamellar structure, preparation method and application thereof

    CN107597146A

  • Photocatalytic material of copper mesh in-situ growth silver particle modified three-dimensional copper sulfide, preparation method and application

    CN111359632A